2021
DOI: 10.3389/fnut.2020.582736
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Prognostic Nutritional Index on COVID-19 Severity

Abstract: Background: The prognostic nutritional index (PNI) has been described as a simple risk-stratified tool for several diseases. We explored the predictive role of the PNI on coronavirus disease 2019 (COVID-19) severity.Methods: A total of 101 patients with COVID-19 were included in this retrospective study from January 2020 to March 2020. They were divided into two groups according to COVID-19 severity: non-critical (n = 56) and critical (n = 45). The PNI was calculated upon hospital admission: 10 × serum albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 43 publications
(34 reference statements)
2
43
5
Order By: Relevance
“… 32 Finally, eight observational studies, with a total of 2002 patients, were included. 8 , 16 , 17 , 33 , 34 , 35 , 36 , 37 However, one study did not report the adjusted OR of PNI as a continuous variable 33 and thus was not included in the meta‐analysis (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 Finally, eight observational studies, with a total of 2002 patients, were included. 8 , 16 , 17 , 33 , 34 , 35 , 36 , 37 However, one study did not report the adjusted OR of PNI as a continuous variable 33 and thus was not included in the meta‐analysis (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the findings of previous efforts, early risk stratification with an accurate and easily calculated parameter is crucial to prevent the progression of COVID‐19. 16 , 17 However, it seems difficult to arrive at the best evidence‐based decision with respect to the current literature, as no prior study had been conducted systematically regarding the impact of the PNI on outcomes and prognosis among COVID‐19 patients. In this study, first, we report the results of our patients to investigate the indicators of in‐hospital mortality and severity in patients with COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“… 31 Immune dysfunction and immunological events caused by SARS‐CoV‐2 are the main mechanisms of progression of COVID‐19 and this suggests that surveillance of the lymphocyte count is valuable for early screening of COVID‐19‐related critical illness. 32 Wang et al 14 first defined PNI as an independent biomarker for the COVID‐19 severity. In the pre‐print study of Doğancı et al, 13 it showed an association between the prognosis and mortality of COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“… 12 There are very few studies, of which one is a pre‐print, investigating the role of PNI in reflecting the inflammatory status and prediction of prognosis in COVID‐19 patients. 13 , 14 Systemic immune‐inflammatory index (SII) is another parameter that reflects the immune and inflammatory status of the organism. 15 SII is a predictor of disease severity and prognosis in patients with tumours, inflammatory diseases, obesity, pulmonary embolism and undergoing primary PCI for acute STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that lower PNI was correlated with a lower survival rate in patients having various malignancies, such as esophageal squamous cancer, colorectal cancer, gastric cancer, and lung cancer [30,31,32]. Nowadays, PNI is an important biomarker that can be used to discriminate COVID-19 severity, according to the results of several studies [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%